Social support of a family and the effect on the population reproduction - A. G. Leontieva (Экономика региона, 2010)
The paper analyzes the problem of reproduction behavior of the population in the context of the demographic crisis. It was proved that deterioration of living conditions causes restriction of reproduction plans of families. By way of example of the Tyumen region quantitative assessment of the influence of the living standard rates on reproduction activity in the region was made. The elaborated factor model of birth rate allowed determining the dynamics of the birth rate for the near term. On the basis of the results obtained a complex of measures aimed at birth rate stimulation was offered.